Unpaid Work in Marine Science: A Snapshot of the Early-Career Job Market - Osiecka, Anna N.; Quer, Susanna; Wróbel, Aleksandra; Osiecka-Brzeska, Katarzyna (Frontiers in Marine Science, 2021)
Unpaid positions in environmental sciences are common yet controversial. While they exclude already marginalised groups and are detrimental to the entire job market, many voices maintain that these positions are crucial, support science and conservation in economically disadvantaged areas, and allow early-career scientists their first step into the field. To better understand the real scale and nature of these positions, we reviewed relevant job offers within marine biology and conservation, advertised globally in English, from three random months in 2019-2020, both preceding and during the COVID-19 pandemic. Unpaid and pay-to-work positions were more common than paid jobs, and offered mostly in economically privileged areas, such as North America and Europe. Most of these postings required some or strong experience and education background. Most non-governmental and private organisations offering uncompensated work did not produce any peer-reviewed research output in the last three years. This review shows that a considerable proportion of unpaid work contributes to private businesses, and may often breach local labour laws.